Gambaran Kebiasaan Makan Masyarakat di Perumahan Allandrew Permai Kelurahan Malalayang I Lingkungan XI Kota Manado - Pandelaki, August J.; Lampus, Benny S.; Kant, Imanuel (UNIVERSITAS SAM RATULANGI, 2013)
Eating habits are behaviors associated with food, one meal frequency, pattern of food eaten, food distribution within the family and how to choose food. Purpose of research was conducted with the aim of eating known picture of scenic urban residential communities allandrew Malalayang I environment XI Manado city. The method of this study include descriptive study using survey method. The population of the whole of society is taken Permai housing environment Allandrew XI aged 25-55 years and amount to as many as 480 people with a sample of 90 people, systematic sampling with a random sampling technique. The data obtained through interviews using a prepared questionnaire. The results obtained rice (55%) bread (38.9%), soybean (78.9%), tahu (97.8%), fish (55.6%), chicken meat (34.4%), pork (65.5%), vegetables (70%), fruits (28.9%), fried bananas (46%), Crepes (50%), malabar (47.8%), tea (52 , 2%), coffee (37%) and milk (18.9). The conclusion of this study concluded that frequent type of food consumed from the staple food is rice and bread, vegetable side dishes are tempeh and tofu, animal side dishes are fish, chicken and pork, vegetables, fruits, food additives such as fried banana, martabak and malabar, while drinks such as tea, coffee and milk. Keywords: Eating Habits